Trade induced growth impacts of corporate entry in the food sector: A case study of fruits and vegetables sub sector in the Punjab State of India - Veena Goel (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Study indicated that the entry of corporate sector in the Punjab State is both in retail and wholesale trade of the fruits & vegetables sub sector. At the organized retail stores these companies have provided its consumers a single window service for the various product assortments while within the fruits & vegetables category (have minuscule scales) widened the product selection choices. Corporate entry in wholesale trade has linked several product specific production belts with medium to high income consumers through various market segments such as organized stores, traditional wholesale/retail markets and the food service. These companies have also provided product variety through imports while opportunities for crop diversification towards higher value crops through exports. In the fruits & vegetables sub sector companies engaged in the retail trade have adopted for short to medium while those in wholesale trade for medium to long-term more sustainable approaches for the sourcing of supplies to build up competitive advantages. This has started generating growth in the Punjab state that has manifested in terms of higher incomes for as the partner farmers and creation of employment for the skilled, semi-skilled and unskilled manpower throughout the supply chain. As the market sizes of these companies expand and diversify in the domestic/global markets it shall enhance growth thereby magnify its impacts.
Keywords: 330; Fruits & vegetables trade; corporate groups; growth